2014
DOI: 10.1002/pits.21792
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Framework for Preventing Perfectionism and Promoting Resilience and Mental Health Among Vulnerable Children and Adolescents

Abstract: Recent findings suggest that perfectionism is highly prevalent among children and adolescents, and perfectionism can be quite destructive in terms of its links with anxiety, depression, and suicide. In this article, we provide an overview of recent research illustrating the costs and consequences of perfectionism among children and adolescents. We also highlight the heterogeneity that exists among perfectionists and the need for a complex, nuanced approach to assessment and prevention that reflects the achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 65 publications
3
72
0
2
Order By: Relevance
“…However, there are few evaluations of such programs in youth, with findings to date suggesting that an explicit focus on reducing perfectionism can indeed be effective, but programs where perfectionism is inserted as part of a general program without an extensive focus on perfectionism, are less effective (Flett & Hewitt, 2014). Only two universal school-based prevention programs directly addressing perfectionism in adolescents have been evaluated with both showing reductions in perfectionism.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…However, there are few evaluations of such programs in youth, with findings to date suggesting that an explicit focus on reducing perfectionism can indeed be effective, but programs where perfectionism is inserted as part of a general program without an extensive focus on perfectionism, are less effective (Flett & Hewitt, 2014). Only two universal school-based prevention programs directly addressing perfectionism in adolescents have been evaluated with both showing reductions in perfectionism.…”
mentioning
confidence: 93%
“…A combination of achieving striving and evaluative concerns is associated with eating disorder symptoms in adolescents (Boone, Soenens, Braet, & Goossens, 2010). The adverse impact of perfectionism, in conjunction with the high prevalence (around 25%) of evaluative concerns in youth (Hawkins, Watt, & Sinclair, 2006), has resulted in a call for school-based prevention of perfectionism and promotion of resilience (Flett & Hewitt, 2014).…”
mentioning
confidence: 99%
“…The developmental changes that occur in adolescence-such as increases in cognitive abilities, self-consciousness, and awareness of social standards-make it a period of elevated susceptibility to evaluative feedback and to others' achievement expectations (Flett & Hewitt, 2014;Flett, Hewitt, Oliver, & Macdonald, 2002). Thus, adolescence is a key period for the study of perfectionism.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst psychological distress is a common topic in university mental health literature, treatment and interventions focused more directly on maladaptive perfectionism may be more client-centred and effective for students with perfectionistic tendencies (Radhu et al, 2012). Consistent with previous findings, the results of this study identified resilience and trait emotional intelligence as important variable to consider for the prevention or control of perfectionism in students (cf., Flett & Hewitt, 2014;Klibert et al, 2014). However, both of these constructs in relation to maladaptive perfectionism are under researched.…”
Section: Discussionmentioning
confidence: 99%